A Historical Study of Himachal Pradesh forts Importance during the Medieval Period: Exploring the Historical Significance of Kangra's Forts and Himachal Pradesh (Journal of Advances and Scholarly Researches in Allied Education, 2021)
The purpose of this study is to the view to have a full concept of the history, antiquity,geography, topography and the connected topics involving the Kangra, its fort and its kings during theancient and mediaeval times.The first zone consists of low hills of the Shiwalik, ranging from Ravi river toYamuna in the south of the region. The second zone comprises of the higher mountains on the height of1200 to 1500 feet cut into steep ravines and precipitous defiles. This zone contains the Dhauladhar andPirPanjal ranges. The third and highly important zone is the Great Himalayas or Northern zone. Itconsists of high mountains and ranges. These ranges are snow clad at a height of 500 to 6000 mts abovesea level. The huge Himalayan peaks separate the drainage of the Spiti from that of the Beas. The Zaskarrange seperatesSpiti and Kinnaur from Tibet. While discussing the geographical characteristics ofHimachal, the rivers of the Pradesh cannot be overlooked. The complete drainage system in the lowlandsprimarily depends upon Himachal Pradesh. Because of the snow-clad peaks of Himachal, the rivers arefull of water throughout the year. The principal channels of drainage in the region are the Chandra-Bhaga, Ravi, Beas, Sutlej and the Yamuna. A significant feature of Himachal Pradesh is its ability tosupply the Indus and Ganga basins. A large chunk of India's terrain is made up of these rivers. Thishelps us better understand the drainage system of the state. Himachal Pradesh has a wide range ofclimates. Some areas of this state are colder than others, such the plains of Punjab, while others arewarmer. The Pradesh also has a wide range of rainfall distributions. There are three distinct seasons inHimachal Pradesh. The forts of Kangra‟s history and antiquity have been subject to numerousspecialised as well as general investigations in the field of archaeology. Nevertheless, the vast majorityof them are about historical events or journeys. Religious texts, Persian histories, numismatic artefacts,epigraphs, travelogues, and contemporary publications are among the materials that can be used.